Optimal NPK Fertilizer Combination Increases Panax ginseng Yield and Quality and Affects Diversity and Structure of Rhizosphere Fungal Communities - Sun, Jin; Luo, Haoming; Yu, Qian; Kou, Baixin; Jiang, Yuxin; Weng, Lili; Xiao, Chunping (Frontiers in Microbiology, 2022)
Soil microorganisms affect crop rhizospheres via transformation and transport of nutrients, which has important influences on soil fertility, carbon sequestration, and plant yield and health in agroecosystems. There are few reports on the effects of fertilizer application on growth of Panax ginseng (C. A. Mey.) or structure of its rhizosphere microbial communities. In this study, an orthogonal experimental design was used to explore the effects of nine different combinations of nitrogen (N), phosphorus (P), and potassium (K) fertilizers with different amounts and proportions on ginseng growth and accumulation of ginsenosides and structure of rhizosphere soil fungal communities. Soil without fertilization was the control. With combined application of NPK, ginseng growth and development increased. Fertilization scheme N3P1K3, with N fertilizer at 50 g·m−2, P fertilizer at 15 g·m−2, and K fertilizer at 60 g·m−2, had the most comprehensive benefit and significantly increased ginseng rhizome biomass and ginsenoside contents (Rg1, Re, Rf, Rg2, Rb1, Ro, Rc, Rb2, Rb3, Rd). Amplicon sequencing showed that NPK application increased diversity of fungal communities in ginseng rhizospheres, whereas richness was bidirectionally regulated by proportions and amounts of NPK. Ascomycota was the dominant fungal phylum in ginseng rhizosphere soil, and relative abundances decreased with NPK combined application. Combined NPK application increased relative abundance of potential beneficial fungi such as Mortierella but decreased that of potential pathogenic fungi such as Fusarium. Correlation analysis showed that potential beneficial fungi were significantly positively correlated with ginseng rhizome yield and ginsenoside contents, whereas the opposite relation was observed with potential pathogenic fungi. Thus, in addition to directly increasing crop growth, precise NPK application can also increase crop adaptability to the environment by shaping specific microbial communities. The results of this study suggest that the combined effects of biotic and abiotic processes on agricultural production determine crop yield and quality.